GW24-e3585 Differentiating vascular dementia from Alzheimer's disease with the Memory and Executive Screening test (MES) - Fang, Li; Qing, Wang (Heart (British Cardiac Society), 2013)
Objectives Alzheimer’ disease (AD) and vascular dementia (VaD) are the most common causes of dementia in the elderly. The Memory and Executive Screening test (MES) is a brief and sensitive screening assessment for cognitive impairment, including the most commonly impaired cognitive domains in dementia, the memory and the executive function. Our aim of the study is to investigate the differentiating ability of MES for mild VaD and mild AD. Methods Three groups of mild VaD, mild AD and normal control were involved. Every group had 30 subjects, matched for gender, age and education. All participant were evaluated by Mini-Mental State Examination (MMSE) and MES. Apolipoprotein E(APOE) genotype was performed in all samples. The vascular factor score (i.e. coronary heart disease, hypertension, stroke, diabetes, hyperlipidemia, alcoholism, every factor was evaluated as 1, the total factor score is the sum of all the factors) were also calculated. Results (1) There was no difference of total cognitive function between the VaD group and the AD group (ADMMSE = 19.6 ± 3.3 vs VaDMMSE = 20.6 ± 5.5, P > 0.05). The vascular factor score and APOE genotyping had significant differences between the VaD group and the AD group (P < 0.01). APOE ε4 was more common in patients with AD(16/30 in AD group vs 5/30 in VaD group, P < 0.01), while vascular factor score were higher in patients with VaD(2.7 ± 1.3 in VaD group vs 0.7 ± 1.0 in AD group, P < 0.01). (2) In the memory portion of MES, VaD patients performed better than AD patients, especially in the item of delay memory (3.8 ± 2.7in VaD group vs 0.5 ± 1.2 in AD group, P < 0.01). In the executive function portion of MES, VaD patients performed worse than AD patients, especially the sequential movement subtest (5.2 ± 3.0 in VaD group vs 7.7 ± 1.9 in AD group, P < 0.01). The ratio of memory and executive function subtest score (MES-R) had significant difference between the two groups (1.2 ± 0.7 in VaD group vs 0.5 ± 0.2 in AD group, P < 0.01). However, there is no difference of the sum of memory and executive function subtest score (i.e. the total score of MES) (47.3 ± 21.6 in VaD group vs 46.0 ± 14.5 in AD group, P > 0.05). (3) The sensitivity of MES-R≤0.7 for differentiating VaD and AD was 76.7% with a specificity of 83.3%,with the area under ROC curve (AUC) is 0.863. The MES-R has the same discriminate ability of vascular factor score (cut-off score = 2, both sensitivity and specificity are 82.8%, AUC = 0.878) and is better than the APOE genotype (83.3% for sensitivity, 53.3% for specificity, AUC = 0.638). Conclusions Most notably executive dysfunction in VaD and memory deficiencies in AD. Individuals with AD typically display impairment on memory recall and recognition while the memory faculties of VaD patients are more intact, yielding some recall deficits and little or no impairment in recognition. Compared to AD patients, VaD patients typically perform considerably poorer on tasks dependent on executive function. MES has two portions in scoring. Fifty score is for memory and fifty for executive function evaluation. The ratio for the two subscale scores will reflect the more impaired domain and will indicate the possible origin of dementia. The value of MES in differentiating VaD from AD proved effectively.